A1 MARKERS OF ACTIVATED INFLAMMATORY CELLS ARE ASSOCIATED WITH NON-ALCOHOLIC FATTY LIVER DISEASE AND INTESTINAL MICROBIOTA. (1st March 2018) - Schwenger, K; Chin, L; Chelliah, A; Da Silva, H; teterina, A; Comelli, E; Taibi, A; Arendt, B; Fischer, S; Allard, J
Abstract: Background: Several mechanisms contribute to the pathogenesis of non-alcoholic fatty liver disease (NAFLD). The intestinal microbiota (IM) and liver immune function cells have been implicated in NAFLD, but data on their potential associations have been scarce. Aims: The aim of this study was to investigate whether there are differences in hepatic inflammatory cell markers between NAFLD and healthy controls (HC), using the antigens CD45, CD163, CD20 and CD3, and to determine whether these markers are associated with specific IM. Methods: This was a prospective, cross-sectional study of adults with biopsy-confirmed NAFLD and healthy controls (HC). Clinical and laboratory data were collected. Fecal IM were assessed by qPCR and immune cells by immunohistochemistry. NAFLD activity score (NAS) was used for disease severity. Results: 42 subjects were studied: 8 HC and 34 NAFLD. Hematopoietic cell marker CD45 + and Kupffer cell marker CD163 + were higher in NAFLD compared to HC, and those with a NAS ≥5 had higher levels of CD20 + cells a marker of B cells versus a NAS of 0 or 1–4. In 39 patients (5 HC, 34 NAFLD) IM was measured: Faecalibacterium prausnitzii was negatively correlated with CD45 + ( r =-0.394, p =0.015) and CD163 + ( r =-0.371, p =0.022) cells in the portal tract; Prevotella was negatively correlated with CD20 + ( r =-0.353, p =0.028) cells in the liver lobule and Archaea were positively correlated with CD20 + ( r =0.468, p =0.003) in the liver lobule. Conclusions: Hepatic immune cell counts are increased in NAFLD versus HC and associated with disease severity. Specific immune cells in portal or lobular areas correlated with specific fecal IM, suggesting a role for IM in hepatic inflammation. Funding Agencies: CIHR